Marital Satisfaction: An Analysis of Long Distance Marriage Couples - Bramana Nanditya Putra; Afdal Afdal (International Journal of Research in Counseling and Education, 2020)
This research aims to describe marital satisfaction of long distance marriage and and the difference marital satisfaction between husband and wife undergoing long-distance marriages(LDM). . This research was a comparative research with a sample number of 45 couples who have LDM. Sample collection withdrawal technique using a purposive sampling technique. This research was measured using a Marital Satisfaction Inventory developed from ENRICH Marital Satisfaction Scale with a few adjustments. The research findings reveal that: (1) marital satisfaction of husband undergoing long-distance marriages is generally in medium category with a percentage of 70.25%, (2) marital satisfaction of wives undergoing LDM is generally in the high category with a percentage of 74.65%, and (3) there is no difference in marital satisfaction between husband and wife undergoing LDM with the value F of 4,940 with probability 0.029 smaller than 0.05.